Ricci Solitons on Lorentzian Four-Dimensional Generalized Symmetric Spaces - Bouharis, A.; Djebbar, B. (Журнал математической физики, анализа, геометрии, 2018)
The existence of non-trivial, i.e., non-Einstein, Ricci solitons on fourdimensional Lorentzian generalized symmetric spaces is proved. Moreover, it is shown that only steady Ricci solitons can be gradient.